An analysis of the role and competency of the Shari'ah Committees (SCs) of Islamic Banks and Financial Service Providers - Hassan, Rusni; Ibrahim, Uzaimah; Abdullah, Nurdianawati Irwani; Abdul Aziz, Akhtarzaitie; Md. Sawari, Mohd. Fuad (International Shari'ah Research Academy for Islamic Finance (ISRA), 2010)
IFSB’s Guiding Principles on Shari'ah Governance Systems for Institutions Offering Islamic Financial Services defines “Shari'ah governance system” as the set of institutional and organisational arrangements through which an institution offering Islamic financial services oversees Shari'ah compliance, i.e., that Islamic banking products and operations are in accord with Shari'ah principles. This requires the establishment of a Shari'ah advisory board. The Shari'ah governance of Islamic financial institutions (IFIs) in Malaysia consists of two components: the Shari'ah apex body, which is the Shari'ah Advisory Council (SAC) established by the Commission, and the Shari'ah advisors appointed by the respective institutions (Shari'ah Committees). Their roles are directing, reviewing, supervising and approving or rejecting the activities of IFIs in order to ensure compliance with Shari'ah rules and principles. The extent to which Islamic banks comply with Shari'ah principles is, to a great extent, determined by the role of such boards. Consequently, this body needs sufficient authority to enable its members to perform their functions effectively. However, many issues have arisen about the role and competency of Shari'ah advisors. This research aims to examine the current practice of Shari'ah advisory in Malaysia from the perspectives of advisors, bankers and regulators. The research focuses on the roles and functions practically played by the Shari'ah advisors and the IFIs’ expectations of them. Problems faced by the Shari'ah advisors, bankers and regulators need to be specifically identified so that measures to bridge the gaps between them may be proposed. This will ensure a harmonious relationship between all stakeholders as well as ensuring that the dayto-day running of IFIs will be compliant with Islamic law.